KEANEKARAGAMAN TUMBUHAN PEKARANGAN DI LINGKUNGAN GETAP, KECAMATAN CAKRANEGARA, KOTA MATARAM - Siratul Aini; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Getap Timur is a village in the Cakranegara District, Mataram City. This study aims to analyze the diversity of yard plant species in Getap. The method used was direct observation of community yards. The data obtained were analyzed using the Shannon-Wiener diversity index (H'). The results showed 15 plant species with a total of 39 individuals. The diversity index (H') value was 2.56, indicating a moderate level of diversity, moderate distribution, and moderate community stability.